Kadar Kolesterol Daging Berbagai Jenis Itik ( Anas domesticus ) Di Kabupaten Semarang - Muliani, Hirawati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Chemical composition of meat is an important factor for human nutrition and contributes to the choice of food by mankind. In recent time humans are much concious of the health benefits of what they consume. The consumption of organic foods, vegetables, fruits, foods high in fibre, foods of animal origin with less fat and cholesterol are among the foods stuffs being upheld. Duck meat is comparable to that of the chicken despite being red meat. Duck meat is high in protein, iron, selenium, and lower calories.This research is aimed to know about meat cholesterol content of Pengging duct, Tegal duck, and Magelang duck. Design of the research was Completely Random Design with 3 treatments, that was 3 kinds of duck and 6 replications. The result showed that there was no significant difference among the meat cholesterol content.